Resistência balística e propriedades de absorção de micro-ondas de um composto feito de tecido de aramida impregnado com polietilenoglicol e nanopartículas de hematita - Carvalho, Danúbia Bordim de (Revista Militar de Ciência e Tecnologia, 2025)
The ballistic resistance and microwave absorption of a composite of aramid fabric impregnated with polyethylene glycol and hematite nanoparticles was investigated for different hematite concentrations between 0 and 17 wt%. Different damage and energy absorbing mechanisms during ballistic impact were identified: cone formation on the back face of the target, tensile failure of primary yarns and deformation of secondary yarns. In terms of energy absorption, the best results were achieved with 7 wt% hematite, while the smallest depth of penetration (DOP) was observed for a composite with 9 wt% hematite. A scanning electron microscope (SEM) image of the composite with 7% hematite after the ballistic test showed that the main energy absorption mechanism was deformation of secondary yarns. Microwave absorption was measured using the waveguide technique in the frequency range from 8 to 12 GHz. Results showed that the dielectric loss ɛ”/ɛ’ is maximum for a concentration of 3% hematite, while the magnetic loss µ”/µ’ is maximum for a concentration of 11 wt% hematite. A reasonable compromise between ballistic resistance and microwave absorption seems to be a composite with 7 wt% hematite.